A Review of Cambridge Advanced Learner’s Dictionary: What Entries Should be Deleted, Revised, and Added? - Rizdika Mardiana (STKIP Muhammadiyah Bogor, 2020)
This article was written to review a dictionary named Cambridge Advanced Learner’s Dictionary (CALD) especially the entries start from actor to adhere. In order to fulfill the readers’ need, some words need to be deleted, revised, and added based on the ways of the dictionary provide the meaning of the words or the ways of the words combine with other words. The consideration of word deletion, revision, and addition was also based on the frequency of the words used by people in in English speaking countries provided by COCA (Corpus of Contemporary American English) and BYU (Brigham Young University). There are three entries should be deleted, 17 entries should be revised, and two entries should be added to CALD.